The handbag : to have and to hold - Allen, Carmel (London Carlton Books, 2012)
According to Carmel Allen, the beauty editor of Vogue magazine, the key to assessing a modern girl is the handbag. With over 150 colour photographs, this book offers a celebration of the handbag.
Include Color Illustration, Index and Acknowledgment
Keywords: Handbags